OOP-AR: Learn Object Oriented Programming Using Augmented Reality - Zulhafiza Zainal Abidin; Muhammad Asyraf Abdullah Zawawi (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2020)
Object-Oriented Programming (OOP) is one of the challenging concept in computer science education especially for novice programmers. To help students understand this concept, this research try to blend OOP with Augmented Reality (AR). The reason because AR can give fun aspect to the learner, which can also help learner to focus longer without distraction. For this research purpose, the target audience is 20 university students with different ability in programming and augmented reality experience. The overall results of this research show that OOP-AR received positive feedback from users. It also proved that OOP-AR is a necessary product for students who need to improvise their knowledge in OOP and its concepts and gain interest in using AR application